Peripheral contrast-enhanced MR angiography at 3.0T, improved spatial resolution and low dose contrast: initial clinical experience. - Nael K; Krishnam M; Nael A; Ton A; Ruehm SG; Finn JP; Nael, Kambiz; Krishnam, Mayil; Nael, Ali; Ton, Anthony; Ruehm, Stefan G; Finn, J Paul (European Radiology, 2008)
To investigate a high spatial resolution peripheral contrast-enhanced MR angiography (CE-MRA) protocol, applying a dedicated multi-channel array coil and accelerated parallel acquisition at 3.0T in evaluation of patients with peripheral vascular disease. Twenty patients with peripheral vascular disease underwent multi-station high spatial resolution peripheral CE-MRA at 3T. The image quality, presence of venous contamination, image noise, and artifact were evaluated by 2 radiologists independently. Assessment of arterial disease for 540 arterial segments was performed, and findings were correlated with conventional catheter angiography in 10 patients. All studies were yielded high diagnostic image quality. Venous contamination and artifact were minimal and never interfered with diagnosis. Sixty seven arterial segments with significant stenoses (>0%) were detected by observers with excellent interobserver agreement (kappa = 0.82; 95% CI: 0.76, 0.88). There was a significant correlation between CE-MRA and conventional angiography (Rs = 0.91 and 0.94 for reader 1 and 2, respectively) for the assessment of the degree of stenosis. Higher available SNR at 3T in combination with multi-coil technology and accelerated parallel acquisition, result in acquisition of nearly isotropic submillimeter 3D voxels throughout the entire peripheral arterial tree with diagnostic image quality and favorable comparative analysis with catheter angiography.